Rolling resistance coefficient of processed roller-skis for skating - Hladnik, J.; Supej, M.; Vodicar, J.; Bizjak, L.; Jerman, B. (2019)
For accurate calculations of the resistance forces and other work-energy calculations during skate roller-skiing on a treadmill the rolling resistance coefficient .. of the roller-skis needs to be determined in dependency of the normal force F[Mu]. In the skating technique the skier rolls side-to-side alternating on one and the other roller-ski, and thus always rolls on a different part of the treadmill surface, which needs to be considered in the measurement of [Mu]. In this study [Mu] of unique processed roller-skis for measurement of the ground reaction forces during skate roller-skiing was measured (a) over time at constant [Mu ] and (b) in dependence from F[Mu], by towing a trolley with attached roller-skis on a treadmill. Changes of [Mu] over 70 minutes resulted in maximally 12%. [Mu] in dependence from Fn rose for 57% for F[Mu] ranging from 141 N to 724 N per roller-ski.